Modelling of spare parts storage strategies for offshore wind - Moritz Jäger-Roschko; Jürgen Weigell; Carlos Jahn (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: The production costs of offshore wind energy are currently very high compared to other means of energy production. During the operational phase of an offshore wind park 17% of the operational costs are logistics cost. To reduce the costs, innovative strategies have to be implemented, like improved spare part strategies. Methodology: In this paper, an agent-based model for the Operation and Maintenance (O&M) supply chain of offshore wind farms is developed analyzing if the storage of spare parts of different offshore wind parts at a central shared warehouse is beneficial. Findings: Shared storage units for two offshore wind farms serviced from different harbours only yield larger profits for large spare parts transported by a crane vessel. For all other components, rapid access and the resulting higher availability of the wind turbines outweigh the cost savings realized by a central warehouse. Originality: The developed model is unique as it comprises two storage levels, two wind parks, and different means of transportation for small, medium, and large spare parts on water and land. Until now, no comparable research exists determining the optimal storage level for spare parts in shared storage infrastructure.
urn:nbn:de:gbv:830-882.054657; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Offshore wind; Operation and maintenance; Agent-based simulation; Spare parts